History and Science of Cultivated Plants - Naithani, Sushma (Open textbook library., 2021)
History and Science of Cultivated Plants narrates how humans transitioned from foragers to farmers and have arrived at present-day industrial agriculture-based civilization. It entails myths, historical accounts, and scientific concepts to describe how human efforts have shaped and produced easier to grow, larger, tastier, and more nutritious fruits, vegetables, and grains from wild plants. Using examples of various economically and socially important crops central to human civilization, the book describes the origin of crop plants, the evolution of agricultural practices, fundamental concepts of natural selection vs. domestication, experimental and methodical plant breeding, and plant biotechnology.